Influence of on Motor Skill Acquisition in Early Childhood - Benjamin Sembiring Benjamin Sembiring; Aris Simaremare; Anugrah Panca Dinata; Franroso Pininggit Simatupang; Boisandi Buulolo; Melisah Melisah (CV. INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: Motor skill development during early childhood is fundamental for physical, cognitive, and social development. Structured play activities have been proposed as effective interventions for enhancing motor skill acquisition in young children. This study investigated the influence of structured play activities on motor skill acquisition among kindergarten students in Medan Deli, North Sumatra, Indonesia. Materials and methods: A total of 120 kindergarten students (aged 4-6 years) participated in this quasi-experimental study. Participants were divided into experimental (n=60) and control groups (n=60). The experimental group engaged in structured play activities for 12 weeks (3 sessions/week, 45 minutes/session), while the control group followed regular curriculum activities. Motor skills were assessed using the Test of Gross Motor Development-3 (TGMD-3) at pre-test and post-test intervals. Results: Statistical analysis using SPSS 28 revealed significant improvements in the experimental group compared to the control group. The experimental group showed substantial gains in locomotor skills (p<0.001, d=1.24) and object control skills (p<0.001, d=1.18). Conclusions: Structured play activities significantly enhance motor skill acquisition in early childhood. Implementation of systematic, play-based motor interventions in kindergarten settings is recommended to optimize developmental outcomes.